Makna Borahae Bagi komunitas Army di Kota Medan - Frimleka Febricia Sihite; Muhammad Iqbal (Universitas Lambung Mangkurat, 2024)
South Korean culture that is very popular among teenagers is Korean drama and K-pop, especially among women. Boygroups and girl groups, are never far from the name Fans. Fans or often called Fandom stands for Fan Kingdom which is a group of fans who form a community based on common interests. Self-identity as a K-pop fan in self-identity formation in K-popers shows that self-identity formation is influenced by social environmental factors, giving an image of affinity groups and idol figures. The formation builds on the side of K-pop exploration and commitment to identity as K-popers. This study aims to see the meaning of BORAHAE for someone who joins the ARMY community in Medan City. The method used in this study is a descriptive qualitative research method with a centralized interview approach. This research was conducted in Medan. This study also aims to find out what BORAHAE means for the ARMY community in Medan City. Data collection techniques are carried out through observation, interviews and documentation from research informants. The results of this study found that the beginning of the word borahae was coined by Kim Taehyung a member of the boy band BTS, and the meaning of the word BORAHAE is an expression of love between BTS idols and ARMY. Borahae loved each other until the end for a long time like the last color of the rainbow which is the